Gender differences in the influencing factors of violent behavior in patients with schizophrenia - Xiaolei Qiu; Lu Wen; Wenqi Jiang; Rongrong Zhang; Hongjun Mao; Shiping Xie (Middle East Current Psychiatry, 2025)
Abstract Background In this study, we investigated the gender differences in the influencing factors of violent behavior in patients with schizophrenia. Methods About 519 patients were evaluated using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and the Positive and Negative Syndrome Scale (PANSS). A regression analysis model was used to investigate the gender-related factors that influence violent behavior in patients with schizophrenia. We also investigated gender differences in cognitive function among schizophrenia patients exhibiting violent behavior. Results We found that male patients are more likely to engage in violent behavior than female patients (57.28 vs. 46.80%). Previous risk behaviors, police-assisted admission, and education were independently associated with violent behavior among male patients, whereas previous risk behaviors, police-assisted admission, and employment status were independently associated with violent behavior among female patients. Moreover, significant differences were found in immediate memory, visuospatial/constructional, language, delayed memory, and total RBANS scores between the violent and non-violent groups among female patients. Prominent differences were found between the two groups in terms of immediate memory and total RBANS scores among males. Conclusion These findings suggested that there are gender differences in the influencing factors and cognition of violent behavior in patients with schizophrenia.